Kwestie kościelne w polsko-czeskich sporach granicznych z lat 1945–1947 - Pałys, Piotr (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article takes up the issue of religious and nationality questions in the Polish-Czech border region after the end of World War II. With regard to the historical, political and international legal context, the author examines the functioning of the Roman Catholic Church structures in the Kłodzko and Racibórz regions, where the influences of the Wrocław, Prague and Olomouc Archdioceses overlapped.
Keywords: Kłodzko county; Racibórz region; Prague Archdiocese; Olomouc Archdiocese; Kłodzko Czechs; Moravians; Polish-Czechoslovakian dispute